The physical and thermal properties of modified rotational molding grade silane cross-linked polyethylene compound - Wan Abdul Rahman, Wan Aizan; Chen, Chan Hoong; Ahmad, Fareed (Penerbit UTM Press, 2007)
This study is aimed at investigating the physical and thermal properties of the modified rotational molding grade cross-linked polyethylene compound with respect to process ability. Rotational molding grade High Density Polyethylene (HDPE) was blended at various compositions with HDPE and Low Density Polyethylene (LDPE) using twin screw extruder. The melt index of the blends was studied according to ASTM D 1238. The blended compositions were chemically cross-linked with various amount of silane cross-linking agent using two roll-mill. Water curing was then undertaken at 100Â°C in water bath for 4 and 8 hours. Gel content was measured according to ASTM D 2765 to determine the degree of cross-linking. For thermal analysis, only samples crosslinked with 2.0 phr silane cross-linking agent were investigated on the Differential Scanning Calorimetry (DSC) according to ASTM D 3417. The thermal stability test of the silane Crosslinkable Polyethylene (XLPE) was performed by Thermogravimetric Analyzer (TGA) according to ASTM D 3850. Results on melt index (MI) indicated that the rotational molding grade HDPE blended with HDPE showed higher MI compared to that with LDPE thus improved process ability. The density of rotational molding grade HDPE with HDPE was slightly increased whereas that blended with LDPE was slightly decreased. Samples blended with HDPE, melting temperature, Tm, barely changed and degree of crystallinity, Xc, decreased with compositions. Samples with LDPE Tm and Xc decreased with compositions thus improved process ability. As the silane concentrations increased, the gel content after curing was also increased but independent of compositions. Longer curing time resulted in higher gel content. Thermal stability of the crosslinked HDPE was higher than the uncross-linked HDPE, thus silane cross-linking help to stabilize the blends.